Effect of Heparin on Insulin-like Activity in Rat Bioassay: Comparison between Rat Diaphragm and Epididymal Fat Pad Assay in Normal and Untreated Diabetic Subjects - Gundersen, Kare; Lin, Boniface J (Diabetes (New York, N.Y.), 1965)
A comparison between the rat diaphragm and the rat epididymal fat pad insulin bioassay has been undertaken, making use of serial dilution on sera from untreated diabetic and normal individuals and preincubation with heparin. Heparin, in our hands, has been found to split isolated basic insulin protein complexes and we believe that it also can do this in diluted sera. Our results indicate that by the use of dilution and preincubation with heparin, the two assays correspond surprisingly well in their results. Untreated diabetics, both in the fasting and postprandial state, have more insulin in their serum than normals. There appears to be an antagonistic factor present in postprandial diabetic serum, which is revealed by dilution. Diabetic sera appear to contain more “complexed insulin” than normal ones. No dissociation of “complexed insulin” could be found when glucose was given orally.